Engineering students' perceptions of team conflict and high-performance teams. (1st January 2014) - Neumeyer, Xaver; McKenna, Ann F.
Our study investigates the role of team conflict in the context of student design project work. We are interested in how students experience conflicts in a team environment and how these conflicts relate to other aspects of teamwork such as communication, division of work, shared goals, and leadership. We are using a mixed-method approach to data collection through peer-review data, team observations, and reflective memos. This paper reports results from a study implemented in a required first-year engineering design course. The majority of participants recognise the benefits that task and procedural conflicts have on team performance. Specifically, teamwork aspects such as communication, open-mindedness, and working towards a common goal were connected to cognitive conflict. The peer-review data illustrates that some class sections showed statistically significant improvements in goal commitment, idea communication during conflicts, conflict engagement and attentive listening over time. The results of the post-hoc tests further suggest that students in teams with a predominantly male composition (three males and one female) reported a statistically significant decrease in goal commitment and attentive listening during the ten-week evaluation period. Finally, methodologically we found that the reflective memos and team observations were better instruments for capturing team conflict, more so than peer-review surveys.